Meeting East Asia: Foreword - Motoh, Helena (Poligrafi, 2019)
The current issue of Poligrafi focuses on this historical period and explores different aspects of the contact with East Asian religions at that time. The text by Chikako Shigemori Bučar focuses on the visits Alma Karlin made to the temples and shrines in Japan and the traces that remain of those visits in her work and her collection. Nataša Vampelj Suhadolnik focuses on how Alma Karlin met with Chinese funerary rituals and mourning practices and how she interpreted them. In the third paper Byoung Yoong Kang provides a detailed reconstruction of the events behind an image in Alma Karlin’s collection that depicts a Korean funeral. In the fourth paper, Klara Hrvatin analyses Japanese musical instruments from the collection of Alma Karlin and their relation to religious music. The last paper, by Helena Motoh, talks about the many ways in which Confucian tradition was understood and interpreted in pre-WWII Slovenia.